Antibody Responses to Severe Acute Respiratory Syndrome Coronavirus 2 in the Serum and Cerebrospinal Fluid of Patients With Coronavirus Disease 2019 and Neurological Symptoms. (21st March 2021) - Cunningham, Janet L; Virhammar, Johan; Rönnberg, Bengt; Dopico, Xaquin Castro; Kolstad, Linda; Albinsson, Bo; Kumlien, Eva; Nääs, Anja; Klang, Andrea; Westman, Gabriel; Zetterberg, Henrik; Frithiof, Robert; et al.
Abstract: Antibody responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in serum and cerebrospinal fluid (CSF) samples from 16 patients with coronavirus disease 2019 and neurological symptoms were assessed using 2 independent methods. Immunoglobulin G (IgG) specific for the virus spike protein was found in 81% of patients in serum and in 56% in CSF. SARS-CoV-2 IgG in CSF was observed in 2 patients with negative serological findings. Levels of IgG in both serum and CSF were associated with disease severity ( P < .05). All patients with elevated markers of central nervous system damage in CSF also had CSF antibodies ( P = .002), and CSF antibodies had the highest predictive value for neuronal damage markers of all tested clinical variables. Abstract : Patients with coronavirus disease 2019 and neurological symptoms had immunoglobulin G against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S/S1 protein in both serum (81%) and cerebrospinal fluid (56%). All patients with elevated markers of central nervous system damage also had immunoglobulin G against SARS-CoV-2 in cerebrospinal fluid.